2007
DOI: 10.1007/s11104-007-9254-0
|View full text |Cite
|
Sign up to set email alerts
|

Saprophytic and pathogenic behaviour of R. solani AG2-1 (ZG-5) in a soil amended with Diplotaxis tenuifolia or Brassica nigra manures and incubated at different temperatures and soil water content

Abstract: Saprophytic and pathogenic behaviour of R. solani AG2-1 (ZG-5) in a soil amended with Diplotaxis tenuifolia or Brassica nigra manures and incubated at different temperatures and soil water content Abstract The Brassicaceae species Diplotaxis tenuifolia and Brassica nigra contain high concentrations of glucosinolates, the precursors of isothiocyanates (ITCs) that can have biofumigation effects in amended soils. In a laboratory experiment, incorporation of these plants as green manures into soil was expected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…The addition of brassicas green manure to soil at 5% concentration suppressed the saprophytic growth of R. solani for about 82–87% comparing to control (no addition), after one month of trial duration [46]. …”
Section: Biofumigation As An Alternative Methods Of Crop Protectionmentioning
confidence: 99%
“…The addition of brassicas green manure to soil at 5% concentration suppressed the saprophytic growth of R. solani for about 82–87% comparing to control (no addition), after one month of trial duration [46]. …”
Section: Biofumigation As An Alternative Methods Of Crop Protectionmentioning
confidence: 99%
“…This process involves growing a Brassica crop (known as the break crop) during the intercrop period and then grinding it up and incorporating the residues into the soil. The direct noxious effect of allelochemicals has been clearly demonstrated in several organisms, but there is increasing evidence to suggest that other mechanisms, such as changes in the structure of soil microbial communities, may have an indirect effect on pathogens, in the long term (Yulianti et al 2007;Mazzola et al 2007). Motisi et al (2009) recently observed temporal changes in the efficiency of control of the soilborne pathogen Rhizoctonia solani by Brassica juncea residues.…”
Section: Effect Of a Cover Crop On Pest Communitiesmentioning
confidence: 99%
“…This chemical reaction produces a number of bio-active metabolites including isothiocyanates, thiocyanates, nitriles, and other sulfur containing compounds (Cole 1976;Sang et al 1984;Mithen 2001;Warton et al 2001;Morra and Kirkegaard 2002). Many factors could contribute to the inconsistency in correlating glucosinolates and their metabolites to disease control because of their differences in toxicity and cumulative availability or persistence in soils (Yulianti et al 2007). For example, depending on the soil type, the half-life of glucosinolates in surface soils (<25 cm depth) under laboratory conditions was 3.5 to 15.5 h (at 20 ºC, Gimsing et al 2006).…”
Section: Introductionmentioning
confidence: 99%